Construction, validity and reliability of the Scale of Teacher Resilience - Guerra, José L. (2013)
Considering that there are no instruments to measure resilience specifically designed for peruvian teachers of elementary and secondary public schools, this study aimed to build an ad hoc instrument based on the theoretical foundations expressed by Henderson and Milstein (2003). We did this based on data from 710 public school teachers, both male and female of Callao region (Peru). The results show that 71 items concentrated around four factors: 1) significant participation, 2) prosocial behavior, 3) self-esteem and learning, and 4) perception of support. The cronbach’s alpha coefficient is of .957, which shows that the resilience scale is highly reliable. The scale has been validated by 10 expert judges.